2020
DOI: 10.1080/07448481.2020.1819293
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol, vapor, or chemicals? College student perceptions of harm from electronic cigarettes and support for a tobacco-free campus policy

Abstract: Objective: This study is the first to examine the influence of e-cigarette emission phrasing on perceived harm of secondhand exposure, and whether harm perception was associated with support for a tobacco-free campus policy. Participants: In the fall 2018 and spring 2019 semesters, 52 sections of a college English course (N ¼ 791 students) were cluster randomized to one of three conditions ("vapor," "aerosol," or "chemicals") assessing harm of secondhand exposure to e-cigarette emissions. Methods: Regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Richard O'Connor, 1 Sarah J Durkin , 2 Joanna E Cohen , 3 Joaquin Barnoya , 4 Lisa Henriksen , 5 Sarah E Hill , 6 Ruth E Malone 7 As public health reckons with the implications of language, word choice and their impacts, [1][2][3] so too does Tobacco Control. Indeed, the editor-in-chief in 2010 pointed to the power of language in bounding discussions in the field.…”
Section: Thoughts On Neologisms and Pleonasm In Scientific Discourse And Tobacco Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Richard O'Connor, 1 Sarah J Durkin , 2 Joanna E Cohen , 3 Joaquin Barnoya , 4 Lisa Henriksen , 5 Sarah E Hill , 6 Ruth E Malone 7 As public health reckons with the implications of language, word choice and their impacts, [1][2][3] so too does Tobacco Control. Indeed, the editor-in-chief in 2010 pointed to the power of language in bounding discussions in the field.…”
Section: Thoughts On Neologisms and Pleonasm In Scientific Discourse And Tobacco Controlmentioning
confidence: 99%
“…This is not hair-splitting, as some evidence suggests 'vapour' is perceived as less harmful than 'aerosol.' 5 Yet, the term has become entrenched in common usage, and even extended to describe a whole retail sector (eg, vape shops).…”
Section: Thoughts On Neologisms and Pleonasm In Scientific Discourse And Tobacco Controlmentioning
confidence: 99%
“…Hence, while both conventional e-cigarettes are often included in a single smokefree or tobacco-free policy, they should be treated as separate products in policy implementation efforts. Studies have shown that colleges rarely communicate e-cigarette risk information or distinguish them in information about university tobacco-free campus policies 33 , yet appropriately tailored messaging about e-cigarette risk may increase perceived harm from e-cigarette use and emissions 34 . For example, in relation to user perceptions in response to the 2019 outbreak of lung injury associated with the use of e-cigarette, or vaping, products (EVALI), which coincided with this period of data collection, a separate study published by the authors found that college respondents using e-cigarettes engaged in various cognitive processes and a range of risk rationalizations in order to justify continued use 35 .…”
Section: Discussionmentioning
confidence: 99%